Inflasi Dalam Perspektif Ekonomi Islam - roza andriani; Gebi Sintia (UNCANG : Journal of Sharia Banking and Islamic Finance, 2025)
Inflation is the general and sustained increase in the prices of goods and services over a certain period, which impacts economic stability and public welfare. This study aims to analyze the perspective of Islamic economics on inflation and the solutions offered by Islam in addressing inflation. The study uses a qualitative approach with secondary data sourced from the Qur'an, Hadith, Islamic economic literature, scientific journals, and related reference books. Data collection techniques were conducted through library research, while data analysis employed descriptive-analytical methods by examining and interpreting inflation concepts from the perspective of Islamic economics. The results of the study indicate that Islam views inflation as a phenomenon that can arise due to imbalances in the real and monetary sectors, the practice of usury, hoarding (ihtikar), and unfair economic distribution. The solutions offered by Islam in addressing inflation include strengthening the real sector, prohibiting usury and speculation, implementing justice in wealth distribution, and the role of the state in maintaining price stability and public welfare. Overall, the Islamic economy offers a preventive and solution-oriented approach to dealing with inflation, based on values of justice and public benefit.